2017
DOI: 10.5194/nhess-2017-437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of extreme weather events on transport infrastructure in Norway

Abstract: clearer understanding of the trends in the development of extreme weather. The studies are based on both historical data and available future scenarios (projections) from climate models. Compared to previous studies, we calculated changes in climate variables that are particularly important in relation to nature hazards. Overall, the analyses document an increase in frequency as well as intensity of both precipitation and wind. Results of projections show that the observed changes will continue throughout this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…We would expect some of the counts to fall outside the confidence interval even if the predicted and observed data have an identical distribution, and the sum of the number of years out of a total of N years with the observed counts outside the predicted interval (n 05 ðtÞÁn 95 ðtÞ) is also expected to follow a binomial distribution for perfect predictions. Figure 9 shows a comparison between predicted number of precipitation events exceeding 10 mm/day [a threshold used by road authorities in Norway (Frauenfelder et al, 2013)] and the counts of observed events. The downscaled results reproduced the realistic multiyear variability with a correlation between the predicted annual median count n m (t) and observed count n o (t) of 0.6.…”
Section: Resultsmentioning
confidence: 99%
“…We would expect some of the counts to fall outside the confidence interval even if the predicted and observed data have an identical distribution, and the sum of the number of years out of a total of N years with the observed counts outside the predicted interval (n 05 ðtÞÁn 95 ðtÞ) is also expected to follow a binomial distribution for perfect predictions. Figure 9 shows a comparison between predicted number of precipitation events exceeding 10 mm/day [a threshold used by road authorities in Norway (Frauenfelder et al, 2013)] and the counts of observed events. The downscaled results reproduced the realistic multiyear variability with a correlation between the predicted annual median count n m (t) and observed count n o (t) of 0.6.…”
Section: Resultsmentioning
confidence: 99%
“…Recent extreme flooding events have blocked roads for extended periods, affected houses, telecommunication, food supply, electricity, and access to hospitals and other medical aids. At least 27% of the public roads in Norway are vulnerable to avalanches and rockslides (Frauenfelder et al 2013). Future scenarios list further increases in flooding as a severe threat (Hanssen-Bauer et al 2017), notably along the coast where the topography is most rugged, rainfall highest, and infrastructure most vulnerable.…”
Section: B the Norway Casementioning
confidence: 99%
“…The data used does not include the correction for undercatch due to the wind, and the relation between the precipitation and elevation is introduced only locally around the station locations. As a result, the predicted precipitation field may potentially underestimate the actual precipitation, especially at higher elevations where the station network is sparser such as at the mountainous region of the southern part of Norway (Frauenfelder et al, 2017;Lussana et al, 2018). Accordingly, we introduced a precipitation correction factor to take this into account so that the long-term water balance is correct.…”
Section: Model Parameters and Calibrationmentioning
confidence: 99%